2022
DOI: 10.1021/acsami.2c08285
|View full text |Cite
|
Sign up to set email alerts
|

Double-Layered Conductive Network Design of Flexible Strain Sensors for High Sensitivity and Wide Working Range

Abstract: For flexible strain sensors, the optimization between sensitivity and working range is a significant challenge due to the fact that high sensitivity and high working range are usually difficult to obtain at the same time. Herein, a breathable flexible strain sensor with a double-layered conductive network structure was designed and developed, which consists of a thermoplastic polyurethane (TPU)/carbon nanotube (CNT) layer (as a substrate layer) and a Ag nanowire (AgNW) layer. The TPU/CNT layer is made of elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…The fibers with diameters of 400–900 nm tend to be randomly aligned due to van der Waals forces during the spinning, forming a disordered and porous isotropic membrane structure with breathability, flexibility, and skin-friendliness. Subsequently, LBL assembly strategy is used in the preparation of conductive network, and the use of a layered structure in crack-based sensors can fully utilize the structural advantages of each layer itself . The sandwich structure of the CNT/MXene/CNT conductive network is coated on the TPU nanofiber by vacuum filtration.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The fibers with diameters of 400–900 nm tend to be randomly aligned due to van der Waals forces during the spinning, forming a disordered and porous isotropic membrane structure with breathability, flexibility, and skin-friendliness. Subsequently, LBL assembly strategy is used in the preparation of conductive network, and the use of a layered structure in crack-based sensors can fully utilize the structural advantages of each layer itself . The sandwich structure of the CNT/MXene/CNT conductive network is coated on the TPU nanofiber by vacuum filtration.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, electrical stability of the CNT/MXene/CNT/TPU strain sensor is further characterized by the I – V curve under different stretching (Figure S6) and the Δ R / R 0 -strain curve at different stretching rates (Figure S7), which enable the sensor to accurately and timely transmit the signals captured in human motion detection to back-end processing equipment. Additionally, the performances of the CNT/MXene/CNT/TPU strain sensor and recent crack-based strain sensors are compared in terms of sensing range and sensitivity (Figure h), ,, and the detailed parameters are shown in Table S1. It can be found that crack-based strain sensors are generally unable to combine a wide sensing range and high sensitivity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations